Field-based tests for determining critical speed among runners and its practical application: a systematic review - Lipková, Lucie; Struhár, Ivan; Krajňák, Jakub; Puda, Dominik; Kumstát, Michal (Frontiers in Sports and Active Living, 2025)
IntroductionThis review focuses exclusively on field-based critical speed (CS) tests for runners, aiming to evaluate key testing conditions to optimize field-based assessments and their practical applications.MethodsA systematic search was conducted in PubMed, Scopus, SPORTDiscus, and Web of Science databases in July 2024 using terms like “critical power,” “critical speed,” “testing,” and “field condition” along with related keywords. Following PRISMA 2020 guidelines, studies were systematically identified, screened, assessed for eligibility, and evaluated for the validity, reliability, and applicability of field-based methods for determining CS in runners.ResultsFrom an initial pool of 450 studies, 19 met the inclusion criteria. The time trial (TT) test and the 3-minute all-out test (3MT) emerged as the most frequently used field-based methods, demonstrating high reliability when conducted under specific conditions.ConclusionThis review demonstrates that while field-based CS testing is a practical alternative to lab-based assessments, obtaining reliable results relies on following recommended testing settings, particularly for TT tests. By outlining the practical applications and conditions necessary for accurate CS assessment, this review supports athletes and coaches in applying CS testing effectively to enhance training strategies and performance.